Analisis Motivasi Kerja yang Dipengaruhi Lingkungan Kerja, Kepuasan Kerja, dan Kompensasi di Sekretariat Daerah Kabupaten Tapanuli Tengah - Antonius Simanjuntak (JUDICIOUS, 2021)
Regional Apparatus Organizations, (OPD), are organizations/institutions within the regional government that are responsible to regional heads consisting of regional secretariats, regional offices/agencies and technical institutions, sub-districts and civil service police units whose existence is adjusted to regional needs. With the many tasks and delegation of authority given by the central government to local governments, OPD are required to work professionally in accordance with good governance. This research was conducted in an effort to analyze how the influence of the work environment, job satisfaction and compensation on the work motivation of employees at the Regional Secretariat of Central Tapanuli Regency. This study used 50 samples and the data were analyzed by multiple linear regression method. The results showed that the work environment, job satisfaction and compensation simultaneously and partially had a positive and significant effect on the work motivation of the employees of the Regional Secretariat of Central Tapanuli Regency. Among the three independent variables used, the biggest influence is given by the variable job satisfaction, followed by the work environment and employee compensation.